Effective behavior change techniques to promote physical activity in adults with overweight or obesity: A systematic review and meta‐analysis - Carraça, Eliana V. (2021)
Multicomponent behavior change interventions are typically used in weight management, but results are largely heterogeneous and modest. Determining which techniques (behavior change technique [BCTs]) are more effective in changing behavior is thus required. This study aimed to identify the most effective BCTs for increasing physical activity (PA) in digital and face-to-face behavior change interventions in adults with overweight/obesity. Four databases were searched for eligible studies until October 2019. BCTs were coded using BCTTv1 and MBCT taxonomies. Sixty-two RCTs were included. Meta-regressions were performed to explore BCTs' moderating role. Five BCTs showed significant moderator effects on PA in digital interventions: goal setting behavior, goal setting outcome, graded tasks, social incentive, and self-monitoring of behavior (adjusted R2 's = 0.15-0.51). One BCT showed significant moderator effects on PA in face-to-face interventions, behavioral practice and rehearsal (adjusted R2  = 0.22). Multivariate and sensitivity analysis generally led to similar findings. Effective BCTs for increasing PA in adults with overweight/obesity in digital and face-to-face interventions seem to differ. Evidence suggests that using goal setting, social incentive, and graded tasks might help improve PA in digital interventions while avoiding inconsistent self-monitoring of behavior. In face-to-face interventions, prompting behavioral practice and rehearsal might lead to better PA outcomes. Still, further studies are needed. Implications of the current findings are discussed.